(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article will discuss a new technology for creating objects and items — a 3D printer. The history of its origin is described, the basic principles and technologies of the device are indicated. A study of the use of a 3D printer is conducted, and the problems and prospects of using this technology in various areas of life are highlighted.